3D bio-inspired hierarchical discontinuous CFRP with enhanced ductility. (15th October 2019) - Rizzo, F.; Pinto, F.; Meo, M.
Abstract: Discontinuous Carbon Fibre Reinforced Polymers (DCFRPs), due to their increased drapability, allow manufacturing of complex components that continuous CFRPs are unable to replicate. However, these materials might have reduced mechanical properties given by the loss of reinforcement continuity. This paper proposes a new bio-inspired pattern configuration of DCFRPs for the improvement of the mechanical properties (e.g. strain to failure and toughness) by exploiting failure mechanisms such as crack deflection and fibres pull-out, while preserving the high formability of DCFRPs. Resin pockets are introduced and arranged in specific three-dimensional patterns to mimic the hierarchical distribution of hard and soft phases typical of several biological systems. Finite Element models for three-point bending and Low-velocity impact tests were developed to optimise patterns and understand failure mechanisms experienced during static and dynamic tests. Experimental tests were carried out on the 3D hierarchical structures to prove its effectiveness in unidirectional and cross-ply CFRP stacking sequences. Good agreement was obtained between the numerical and experimental results especially in the prediction of the absorbed impact energy. The results demonstrated the effectiveness of the bio-inspired solution in improving the absorbed impact energy of CFRP while increasing drapability of existing prepreg materials.